(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the environmental factors and their positive and negative effects on quality of life? Purpose: The purpose of the research is to identify the key effects of modern quality of life factors. The aim of the research is to study the concept of quality of life and its effects and to create a quality of life model based on quality of life factors. Method: A qualitative method of review and analysis of scientific and professional literature in the field of quality of life is used. For the purposes of the research, we used works published between 2000 and 2022. Results: Based on a review of the literature, a model of quality of life with eight dimensions or factors was created - social interactions, natural environment, lifestyle, professional and private life, employment status and income inequality, social protection, information and communication technologies and COVID-19. At least 26 positive and 37 negative effects of the environment on the quality of life have been identified. Organization: The research contributes to organizations by recognizing modern environmental factors and their effects on the quality of life, whereby organizations can mitigate some of the negative effects. Society: The research contributes to the knowledge of the positive effects of the environment on the quality of life and raises awareness of the more or less favorable reality of the effects of the environment on the quality of life of modern society. By becoming aware of certain negative effects, each individual can contribute to a better quality of his life and the lives of others. Originality: The originality of the research lies in contributing to awareness and possibly mitigating the negative effects of the environment on the quality of life. Limitations/Future Research: The research is limited to a literature review only, which represents certain limitations in the amount of data.